Maximum growth and survival of estrogen receptor-alpha positive breast cancer cells requires the Sin3A transcriptional repressor - Alarid Elaine T; Ellison-Zelski Stephanie J (Molecular Cancer, 2010)
Abstract Background Sin3A is an evolutionarily conserved transcriptional repressor which regulates gene expression as part of the multi-protein Sin3 repressive complex. It functions as a scaffold upon which proteins with enzymatic activity dock, including chromatin modifying histone deacetylases. Although regulation of transcription by Sin3A has been studied in detail, little is understood about the function of Sin3A in cancer cells. We previously showed that Sin3A is expressed in breast cancer cells and is a repressor of estrogen receptor-alpha (ERα, ESR1) gene expression. Here, we expand our previous studies to elucidate the function of Sin3A in the control of gene expression and growth of breast cancer cells. Results Analysis of gene expression following knockdown of Sin3A revealed changes in both basal and regulated gene transcription. Genes of known importance in breast cancer and estrogen signaling, including ERBB2, PGR, MYC, CLU, and NCOA2, were among those identified as Sin3A-responsive. The mechanism of Sin3A action varied among genes and was found to be mediated through both HDAC1/2 -dependent and -independent activities. Loss of Sin3A inhibited breast cancer cell growth by increasing apoptosis without affecting cell cycle progression. Analysis of both ERα-positive and ERα-negative cell lines revealed that the effects of Sin3A on growth were cell-type specific, as Sin3A expression promoted maximum growth of only the ERα-positive cells, and, notably, Sin3A protein itself was increased by estrogen. Further gene expression experiments revealed that Sin3A repressed expression of key apoptotic genes, including TRAIL, TRAILR1, CASP10, and APAF1, in ERα-positive, but not ERα-negative, cell lines, which could provide a mechanistic explanation for cell-type differences in growth. Conclusions This study identifies Sin3A as a regulator of gene expression, survival, and growth in ERα-positive breast cancer cells. Sin3A regulates the transcription of genes involved in breast cancer and apoptosis and acts through multiple mechanisms not limited to histone deacetylase function. These findings reveal previously undescribed functions of Sin3A in breast cancer and provide evidence for an important role of this transcriptional repressor in ERα-positive tumor cell growth.